Ancient Hebrew Wedding Culture Concept And Its Typology With Second Coming - Wahyoe Rita Wulandari (Green Publisher Indonesia, 2022)
The Church is betrothed to Christ much the same way as betrothal in Jewish custom. The Jewish betrothal was done by gold or sum of money. Christ as the Bridegroom has sealed the betrothal of marriage by his own blood. The shared cup of wine symbolized the sealing of their marriage covenant in blood. Christ paid the mohar with His blood. The mohar consisted of a payment to the bride's father and emphasized the binding aspect of the betrothal between the two families. After the betrothal ceremony there was period of separation between the bride and groom. This usually lasted about a year. During which the groom prepared a chuppah, bridal canopy. This was a room attached to his father's house and would have been beautifully decorated for the bride (John 14:1-4). After the betrothal period the groom would bring his bride to this room. The groom could not return for his bride until his father said that the chuppah was ready. All Christians should be watching and waiting for the appearance of the Bridegroom the Lord Jesus. When Christ comes to claim His bride and take the Church to the Father’s house. The Marriage Supper follows as the third and final step and is a glorious celebration of all who are in Christ Jesus (Rev. 19:7).